Comparison of the utility of everyday memory test and the Alzheimer's Disease Assessment Scale‐Cognitive part for evaluation of mild cognitive impairment and very mild Alzheimer's disease. Issue 3 (15th April 2013) - Adachi, Hiroyoshi; Shinagawa, Shunichiro; Komori, Kenjiro; Toyota, Yasutaka; Mori, Takaaki; Matsumoto, Teruhisa; Sonobe, Naomi; Kashibayashi, Tetsuo; Ishikawa, Tomohisa; Fukuhara, Ryuji; Ikeda, Manabu
<x xml:space="preserve">Abstract</x> Aim The purpose of this study was to compare the utility of the Rivermead Behavioural Memory Test (RBMT) and the Alzheimer's Disease Assessment Scale‐Cognitive part (ADAS‐Cog) for the evaluation of mild cognitive impairment (MCI) or very mild Alzheimer's disease (AD). Methods The discriminative abilities of RBMT and ADAS‐Cog were compared in the very early stage of AD or MCI patients. Furthermore, we evaluated the difference in both RBMT score and ADAS‐Cog score between different severities. Results Evident superiority in the false negative rate was observed in RBMT over ADAS‐Cog in MCI or very mild AD. In addition, 86.7% of the subjects overlooked by ADAS‐Cog were correctly detected by RBMT profile score. However, the RBMT score falls in the very early stages and the range of the RBMT score is rather narrow. As a result, it is difficult to evaluate status and follow the progression in severer cases. In contrast to RBMT, the ADAS‐Cog score has a wide range and can evaluate and follow the severity in more severe cases. Conclusion RBMT is more useful than ADAS‐Cog in evaluating patients with MCI or very mild AD.